Implementasi Jual Beli Melalui Sistem Dropshipping Dalam Bisnis Digital Syariah: Perspektif Fiqih Muamalah - Nur Atika; Muhammad Yazid (Jaanur Elbarik Indonesia, 2025)
This study aims to analyze the implementation of the dropshipping sales system in digital businesses from the perspective of Islamic jurisprudence (fiqh muamalah) and to identify the appropriate form of contract to comply with Sharia principles. This study uses a qualitative descriptive method with a library study approach, reviewing classical and contemporary literature, scientific journals, and fatwas related to the dropshipping system. The results of this study conclude that the dropshipping business model can be considered Sharia-compliant if it is implemented using a valid contract and is based on the values ​​of justice, honesty, transparency, and the common good.